A study on thermomechanical interactions in two-dimensional tissues without energy dissipation - Areej Almuneef; Ibrahim Abbas; Alaa A. El-Bary (Case Studies in Thermal Engineering)
This work analyzes the thermomechanical responses of two-dimensional living tissue to immediate heating without energy dissipation. To effectively use thermal treatment methods and techniques, one must have a thorough comprehension of heat transport and the associated mechanical and thermal impacts on the biological tissue of the patient. An exponentially decaying pulse describes a heat flux across the half-space surface under a condition of zero traction with that boundary. The eigenvalue approaches are used to obtain analytical solutions with Fourier-Laplace transformations. The inversion processes for the Laplace and Fourier transforms are implemented using a numerical programming approach, specifically employing the Stehfest numerical inverse approach. The findings indicate that all the analyzed distributions have large sensitivities to pulsing heat flux time and blood perfusion rate.